The Effect Of Sustainable Performance On Capital Structure : Case Of High Tech Companies In Indonesia - Agus Triyani; Wulan Budi Astuti; Suhita Whini Setyahuni; Salsabilla Putri (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2023)
Sustainability performance plays an important role in the business entities. Recently, stakeholders are no longer focus on the single financial performance, but rather put their attention on the business sustainability comprehensively. Since the high-tech companies have the high level of innovation and high uncertainties, sustainability performance received more attention from business practitioners. The high technology in the company can greatly improve the world economy because it greatly affects the potential for global competitiveness. This study intends to examine the effect of sustainability performances on the capital structure of High-Tech Companies in Indonesia. High-Tech Companies faced uncertainty and high-risk in collecting capital due to market issues, a lack of resources, and also issues in technology implementations. Therefore, High-Tech Companies are facing sustainability performances issues that might affect capital structures. We analyzed 143 High-Tech Companies in Indonesia. We identified factors that affect capital structure of High-Tech Companies, such as firm performances, firm growth and CSR performances. Firm performances were measured by ROA and ROE, while firm performances were measured by asset growth and sales growth, and CSR performances were measured by employees, social, and environmental aspects. The result indicated that ROA and ROE were negatively impacted the capital structure of High-Tech Companies. Meanwhile, CSR performances and asset growth were positively affected the capital structure of the companies. In addition, sales growth has no effect on capital structure of High-Tech Companies. Our research used a new perspective of CSR performances that used more comprehensive indicators which are employees, social, and environmental individually. Our findings contributed to the development of legitimacy theory which focus on capital structure and sustainability aspects.